Decolorization of RBBR by plant cells and correlation with the transformation of PCBs - Chroma, Ludmila; Macek, Tomas; Demnerova, Katerina; Macková, Martina (Chemosphere, 2002)
An extracellular H2O2-requiring Remazol Brilliant Blue R (RBBR) decolorizing enzyme activity was detected after cultivation of cells of various plant species both in liquid medium and when growing on agar plates containing RBBR. Level of the enzyme activity was compared with the ability to metabolize polychlorinated biphenyls (PCBs). The ability to decolorize RBBR was tested in the presence and absence of PCBs. The cultures with high PCB-transforming activity proved to exhibit RBBR oxidase much more resistant towards the influence of PCBs. In addition low activities of lignin peroxidase (LiP) and manganese dependent peroxidase (MnP) were detected in medium and in plant cells. No correlation of MnP and LiP activities with PCB degradation could be found. The RBBR decolorization could be used as a rough screening method for plant cultures able to metabolize PCBs.
Keywords: anthrachinony; polychlorované bifenyly; Biodegradation, Environmental; Solanum; Coloring Agents; látky znečišťující životní prostředí; biodegradace; Polychlorinated Biphenyls; Anthraquinones; Environmental Pollutants; barvicí látky